The pathogenesis of post-stroke osteoporosis and the role oxidative stress plays in its development - Li, JinYan; Shi, Lin; Sun, JianMin (Frontiers in Medicine, 2023)
Cardiovascular disease and osteoporotic fractures (OF) are the main diseases affecting the health of middle-aged and elderly people. With the gradual increase of population aging in China and even the world, the incidence of the two and the prevalence of high-risk groups are also showing a continuous upward trend. The relationship between the two, especially the impact of cardiovascular disease on the risk and prognosis of OF, has attracted more and more attention. Therefore, it is of great significance to fully understand the pathogenesis of cardiovascular and cerebrovascular diseases and the resulting osteoporosis and to provide targeted interventions to prevent the occurrence of diseases and fractures. This article reviews the relationship between one of the Cardiovascular disease—stroke and related therapeutic drugs and the risk of OF, and the role of oxidative stress in its pathophysiological mechanism by reviewing relevant domestic and foreign literature in recent years, in order to gain a more comprehensive understanding of the association between stroke and OF, and then provide a basis and reference for screening high-risk groups of fractures and reducing the burden on the health system caused by the disease.